Preparation process of heat-resistant antibacterial PLA (polylactic acid) full-biodegradable straw
By using a combination of polyL-lactic acid and polyD-lactic acid in PLA straw, adding antioxidants and other ingredients, and using blended melt granulation and other processes, the problem of low thermal deformation temperature of PLA straw is solved, and heat resistance is achieved Antibacterial all-biodegradation straw.
Patent Information
- Application Number
- CN202411597310.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional polypropylene straws cannot degrade in the natural environment, and the thermal deformation temperature of PLA straws is low, limiting their heat resistance applications.
Using a combination of polyL-lactic acid and polyD-lactic acid, an antioxidant, chain extender, plasticizer, etc., the process of blending melt granulation, slice drying, melt spinning, drafting, heat setting and curling, Prepare a heat-resistant and antibacterial PLA full biodegradation pipette.
The thermal stability of the PLA straw is improved, allowing it to be used at temperatures up to 120°C while maintaining the biodegradability and antibacterial properties of the material.
Smart Images

Figure CN119432028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new material processing, and in particular to a preparation process of a heat-resistant and antibacterial PLA fully biodegradable straw. Background Art
[0002] Straws are common products in people's daily lives. They are widely used in food, catering, and medicine, bringing great convenience to people's lives. However, traditional straws are made of plastic materials such as polypropylene, which cannot be degraded in the natural environment. The large-scale use and disposal of disposable straws has caused great harm to the soil, atmosphere, and ocean. With the rapid development of my country's takeout, tea and other industries, the demand for disposable plastic straws has increased sharply. According to big data, 1.5 billion disposable plastic straws can be used nationwide in one day. It can be seen that the development of an environmentally friendly plastic straw is extremely important for environmental protection and industrial development.
[0003] Biodegradable plastic straws can meet the above requirements. Among them, polylactic acid (PLA) is a good material for preparing biodegradable plastic straws. It comes from biomass such as starch and cellulose. After being discarded, it can be degraded into carbon dioxide and water by composting under the action of microorganisms. It is a bio-based and fully biodegradable green polymer material. The performance of PLA is very close to that of polypropylene. When used as a straw, it has sufficient strength and hardness, good water resistance and solvent resistance, and is non-toxic and odorless.
[0004] However, PLA has a very slow crystallization rate. During industrial production, the heat deformation temperature (HDT) of PLA products is only about 58°C. Polylactic acid products are difficult to process, and its film products cannot be used to hold, cover, or package high-temperature items. Among plastic products, when used as packaging containers, they cannot be used in lunch boxes, soup bowls, tea cups, and other containers that need to be used under high temperature conditions. They are also not suitable for containers heated in microwave ovens and have poor heat resistance, which limits the heat-resistant application of PLA straws. Summary of the invention
[0005] The object of the present invention is to provide a process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw to solve the above-mentioned defects caused by the prior art.
[0006] A heat-resistant and antibacterial PLA fully biodegradable straw, comprising the following raw materials of a polylactic acid biological straw: 60-75 parts of poly L-lactic acid; 25-40 parts of poly D-lactic acid; 0.1-0.2 parts of an antioxidant 1010; 0.2-0.4 parts of a chain extender ADR4380; 1-3 parts of a plasticizer acetyl tributyl citrate; the total amount of the poly L-lactic acid and the poly D-lactic acid is 00 parts;
[0007] The preparation process includes blending, melting and granulating the raw materials, slicing, drying, melt spinning, drawing, heat setting and curling;
[0008] The blending melt granulation comprises the following steps: (1) mixing poly-L-lactic acid, poly-D-lactic acid, an antioxidant and a chain extender and drying the mixture, wherein the chain extender is one or more of ADR4300, ADR4368 and ADR4380;
[0009] (2) adding a plasticizer and then performing melt granulation to obtain stereocomposite polylactic acid slices;
[0010] (3) The screw temperature of the melt granulation is 210°C 230°C, the speed is 300r / min 400r / min and has the characteristic of being completely degradable 12;
[0011] (4) The uniformly mixed raw materials are passed through an extruder, extruded by a screw, and formed into a hollow long strip straw through a die under high temperature conditions.
[0012] A heat-resistant and antibacterial PLA fully biodegradable straw preparation process, mixing and modification treatment: PLA is mixed with other biodegradable materials such as PBAT, lubricants, antioxidants, etc., and modified.
[0013] The specific steps include measuring talc powder into a high-speed hot mixer for dehydration, then adding tetrabutyl phthalate and phthalic acid composite material for low-speed stirring,
[0014] Finally, the modified material is put into a cold mixing pot and added with PLA, PBAT and other materials, and mixed, melted and quantitatively extruded through twin-screw extrusion to form a masterbatch.
[0015] Take 300-330 grams of plant fiber, add 1.5-1.6 liters of deionized water, soak and wash, and then place in 900-950 ml of sodium hexametaphosphate solution with a mass concentration of 0.6-0.8% and stir and disperse at a speed of 400-500 rpm for 10-15 minutes.
[0016] Then, ultrasonic dispersion is performed for 5-10 minutes, and filtration is performed. The filtrate is dried in a drying oven at 80-85° C. for 5-7 hours to obtain the treated modified plant fiber.
[0017] Extrusion molding: The mixed raw materials are passed through an extruder, extruded by a screw, and formed into a hollow long straw through a die under high temperature conditions. This process is called one-shot extrusion molding.
[0018] Cooling and cutting: Set the preheating temperature of the open mixer to 185-190°C for 40-50 minutes, raise the temperature to 210-220°C, and heat and blend for 10-12 minutes. Introduce the extruded straws into a water tank for cooling to solidify and cool them down. Cut the cooled straws with a cutting machine and set the length of the straws as needed.
[0019] Inspection and packaging: The cut straws are inspected for quality, including inner diameter, thickness, length, roundness and other indicators. The qualified straws are finally packaged by the packaging machine to ensure the hygiene and integrity of the product.
[0020] Preferably, the moisture content of the talcum powder is controlled to be below 0.01%.
[0021] Preferably, the moisture content of the dried raw material is ≤100 ppm.
[0022] Preferably, the screw temperature for heating and melting is 240°C-255°C.
[0023] Preferably, the temperature of the ionized water is in the range of 45-50°C.
[0024] Preferably, the plant fiber has a length ranging from 40 to 60 microns.
[0025] Preferably, the soaking time of the plant fiber is in the range of 20-30 minutes.
[0026] Preferably, the temperature for stretching the straw is 75° C.-85° C., and the stretching multiple is 3-5 times.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] 1. Polylactic acid is used as the matrix, and the prepared synergistic particles are added and blended with the processed modified plant fibers to obtain a composite high-performance material for preparing straws, which reduces the proportion of polylactic acid, reduces costs, ensures the mechanical properties of the straw material, and solves the problem that the existing polylactic acid straws are brittle and difficult to process;
[0029] 2. By designing different twin-screw combinations, controlling the thermal balance and heat conduction of the mold, improving processing equipment and processes, ensuring that PHA is in an isothermal crystallization state during the pressure holding and cooling molding stages, further improving the crystallization rate of PHA during the processing, shortening the molding cycle, and effectively improving the thermal decomposition of PHA during the processing, the heat-resistant and degradable straws made of PHA products with excellent comprehensive performance can usually be used at temperatures as high as 120°C, and because the raw materials come from nature, they are also more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a data diagram of an embodiment of the present invention DETAILED DESCRIPTION
[0031] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0032] like Figure 1 As shown, a process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw includes the following components: 60-75 parts of poly L-lactic acid; 25-40 parts of poly D-lactic acid; 0.1-0.2 parts of antioxidant 1010; 0.2-0.4 parts of chain extender ADR4380; 1-3 parts of plasticizer acetyl tributyl citrate; the total amount of the poly L-lactic acid and the poly D-lactic acid is 00 parts;
[0033] The preparation process includes blending, melting and granulating the raw materials, slicing, drying, melt spinning, drawing, heat setting and curling;
[0034] The blending melt granulation comprises the following steps: (1) mixing poly-L-lactic acid, poly-D-lactic acid, an antioxidant and a chain extender and drying the mixture, wherein the chain extender is one or more of ADR4300, ADR4368 and ADR4380;
[0035] (2) adding a plasticizer and then performing melt granulation to obtain stereocomposite polylactic acid slices;
[0036] (3) The screw temperature of the melt granulation is 210°C 230°C, the speed is 300r / min 400r / min and has the characteristic of being completely degradable 12;
[0037] (4) The uniformly mixed raw materials are passed through an extruder, extruded by a screw, and formed into a hollow long strip straw through a die under high temperature conditions.
[0038] Mixing and modification: PLA is mixed with other biodegradable materials such as PBAT, lubricants, antioxidants, etc., and modified.
[0039] The specific steps include measuring talc powder into a high-speed hot mixer for dehydration, then adding tetrabutyl phthalate and phthalic acid composite material for low-speed stirring,
[0040] Finally, the modified material is put into a cold mixing pot and added with PLA, PBAT and other materials, and mixed, melted and quantitatively extruded through twin-screw extrusion to form a masterbatch.
[0041] Take 300-330 grams of plant fiber, add 1.5-1.6 liters of deionized water, soak and wash, and then place in 900-950 ml of sodium hexametaphosphate solution with a mass concentration of 0.6-0.8% and stir and disperse at a speed of 400-500 rpm for 10-15 minutes.
[0042] Then, ultrasonically disperse the mixture for 5-10 minutes, filter the mixture, and dry the resulting filtrate in a drying oven at 80-85° C. for 5-7 hours to obtain the treated modified plant fiber;
[0043] Extrusion molding: The mixed raw materials are passed through the extruder, extruded by the screw, and formed into a hollow long straw through the die under high temperature conditions. This process is called one-time extrusion molding process
[0044] In this embodiment, preferably, the moisture content of the talcum powder is controlled to be below 0.01%.
[0045] In this embodiment, the moisture content of the dried raw material is ≤100 ppm.
[0046] In this embodiment, the screw temperature for heating and melting is 240°C-255°C.
[0047] In this embodiment, the temperature range of the ionized water is 45-50°C.
[0048] In this embodiment, the plant fiber has a length ranging from 40 to 60 microns.
[0049] The soaking time of the plant fiber ranges from 20 to 30 minutes.
[0050] In this embodiment, the temperature of the straw stretching is 75° C.-85° C., and the stretching multiple is 3-5 times.
[0051] 1) Extract α-cellulose from plant raw materials, swell it, and shear it with high-speed machinery to prepare nano-microfibrillated cellulose.
[0052] The specific process is as follows: first, the plant fiber is crushed into 50 mesh particles, bleached with 10% mass fraction of sodium chlorite
[0053] After being treated with whitening for 1 hour, the cellulose was dried, and then treated with 5% by mass sodium hydroxide for 1 hour, filtered, and washed with water until neutral to obtain a-cellulose; secondly, the a-cellulose was added to a urea-alkali solution at a solid-liquid ratio of 1:5 for swelling treatment for 3 hours at a treatment temperature of 50°C to obtain swollen a-cellulose, wherein the mass ratio of sodium hydroxide, urea and pure water in the urea-alkali solution was 5:10:80; finally, the swollen a-cellulose was sheared by high-speed machinery for 1.5 hours, and then washed with water at a speed of 8000 rpm until neutral, and the precipitate was freeze-dried to obtain white nano-microfibrillated cellulose;
[0054] 2) Preparation of carboxylated nano-microfibrillated cellulose grafted chitosan: a) preparing nano-microfibrillated cellulose, chitosan, ammonium persulfate, chloroacetic acid, water, an alkaline catalyst, an esterifying agent and a second coupling agent in a mass ratio of 80:3:200:15:400:5:1.5:1;
[0055] b) adding the prepared nano-microfibrillated cellulose, chitosan, ammonium persulfate, chloroacetic acid and water into the ball mill of a planetary ball mill for ball milling, using zirconium oxide or ceramic balls as the grinding medium, the temperature is 50°C, the ball mill revolution speed is 100 rpm, the rotation speed is 150 rpm, and the ball milling time is 80 min;
[0056] c) After step b), the prepared alkaline catalyst, esterification agent and second coupling agent are added into the ball mill, and the grinding is continued at a temperature of 60°C, a ball mill revolution speed of 100 rpm, a rotation speed of 180 rpm, and a ball milling time of 100 min; d) After step c), the powder in the ball mill is taken out and placed in a drying oven, and dried at 105°C until absolutely dry to obtain carboxylated nano-microfibrillated cellulose grafted chitosan;
[0057] 3) polylactic acid, inorganic filler, carboxylated nano-microfibrillated cellulose grafted chitosan, a first coupling agent, an antioxidant and a lubricant are uniformly mixed at high speed to obtain a premix; the specific process is: firstly, the polylactic acid is dried at 50-80°C to absolute dryness, and the inorganic filler is dried at 80-105°C to absolute dryness, and then the inorganic filler, the first coupling agent, the antioxidant and the lubricant are mixed at a low speed of 200 rpm for 8 minutes to obtain a mixture, and then the polylactic acid and carboxylated nano-microfibrillated cellulose grafted chitosan are added to the mixture, and the mixture is mixed at a high speed of 500 rpm for 10 minutes at a temperature of 60°C to obtain a premix;
[0058] 4) melt-blending the obtained premix, extruding it, cooling and cutting it, and annealing it to obtain the heat-resistant and antibacterial PLA fully biodegradable straws; the specific process is: placing the obtained premix in a twin-screw extruder or an internal mixer for melt-blending, and then extruding and granulating it at 160'C to obtain blended pellets; then placing the obtained blended pellets in a single-screw extruder, extruding it through a circular die at 140"C, cooling it to 20"C, and cutting it into straws; then subjecting the obtained straws to infrared heating annealing at 100°C for 5 minutes to obtain heat-resistant and antibacterial PLA fully biodegradable straws.
[0059] Therefore, the embodiments disclosed above are only illustrative in all aspects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
Claims
1. A heat-resistant and antibacterial PLA fully biodegradable straw, characterized by: The raw materials of the polylactic acid biological straw include the following components: 60-75 parts of poly L-lactic acid; 25-40 parts of poly D-lactic acid; 0.1-0.2 parts of antioxidant 1010; 0.2-0.4 parts of chain extender ADR4380; 1-3 parts of plasticizer acetyl tributyl citrate; the total amount of the poly L-lactic acid and the poly D-lactic acid is 00 parts; The preparation process includes blending, melting and granulating the raw materials, slicing, drying, melt spinning, drawing, heat setting and curling; The blending melt granulation comprises the following steps: (1) mixing poly-L-lactic acid, poly-D-lactic acid, an antioxidant and a chain extender and drying the mixture, wherein the chain extender is one or more of ADR4300, ADR4368 and ADR4380; (2) adding a plasticizer and then performing melt granulation to obtain stereocomposite polylactic acid slices; (3) The screw temperature of the melt granulation is 210°C 230°C, the speed is 300r / min 400r / min and has the characteristic of being completely degradable 12; (4) The uniformly mixed raw materials are passed through an extruder, extruded by a screw, and formed into a hollow long strip straw through a die under high temperature conditions.
2. A process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw, characterized by: Mixing and modification: PLA is mixed with other biodegradable materials such as PBAT, lubricants, antioxidants, etc., and modified. The specific steps include measuring talc powder into a high-speed hot mixer for dehydration, then adding tetrabutyl phthalate and phthalic acid composite material for low-speed stirring, Finally, the modified material is put into a cold mixing pot and added with PLA, PBAT and other materials, and mixed, melted and quantitatively extruded through twin-screw extrusion to form a masterbatch. Take 300-330 grams of plant fiber, add 1.5-1.6 liters of deionized water, soak and wash, and then place in 900-950 ml of sodium hexametaphosphate solution with a mass concentration of 0.6-0.8% and stir and disperse at a speed of 400-500 rpm for 10-15 minutes. Then, ultrasonically disperse the mixture for 5-10 minutes, filter the mixture, and dry the resulting filtrate in a drying oven at 80-85° C. for 5-7 hours to obtain the treated modified plant fiber; Extrusion molding: The mixed raw materials are passed through an extruder, extruded by a screw, and formed into a hollow long straw through a die under high temperature conditions. This process is called one-shot extrusion molding. Cooling and cutting: Set the preheating temperature of the open mixer to 185-190°C for 40-50 minutes, raise the temperature to 210-220°C, and heat and blend for 10-12 minutes. Introduce the extruded straws into a water tank for cooling to solidify and cool them down. Cut the cooled straws with a cutting machine and set the length of the straws as needed. Inspection and packaging: The cut straws are inspected for quality, including inner diameter, thickness, length, roundness and other indicators. The qualified straws are finally packaged by the packaging machine to ensure the hygiene and integrity of the product.
3. The process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw according to claim 1, characterized in that: The moisture content of the talcum powder is controlled to be below 0.01%.
4. The process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw according to claim 1, characterized in that: The moisture content of the dried raw material is ≤100 ppm.
5. The process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw according to claim 1, characterized in that: The screw temperature for heating and melting is 240°C-255°C.
6. The process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw according to claim 2, characterized in that: The temperature of the ionized water is in the range of 45-50°C.
7. The process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw according to claim 2, characterized in that: The plant fiber has a length ranging from 40 to 60 microns.
8. The process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw according to claim 2, characterized in that: The soaking time of the plant fiber ranges from 20 to 30 minutes.
9. The process for preparing a heat-resistant and antibacterial PLA fully biodegradable straw according to claim 2, characterized in that: The temperature for drawing the straw is 75° C.-85° C., and the drawing multiple is 3-5 times.